2006
DOI: 10.1007/s10897-006-9020-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient Satisfaction with Telehealth and On‐Site Consultations: A Pilot Study for Prenatal Genetic Counseling

Abstract: Many different fields of medicine are now utilizing video conferencing as a means to offer consultations to individuals in rural communities. However, there is a lack of published literature regarding the use of telehealth in clinical genetics and, specifically, in genetic counseling. Those experiences that have been reported mostly centered on cancer genetic counseling, sickle cell anemia consultation and care, or pediatric/adult genetic assessment. In these studies, the patients reported an overall satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 14 publications
5
73
0
2
Order By: Relevance
“…The studies included in our review related to the use of telegenetics in counseling for hereditary cancer, 26,[28][29][30][31][32][33] prenatal counseling, 34 pediatric services, 35,36 and services for a range of genetic disorders. 24,27,37 Of the 125 patients who were evaluated and/or counseled via telemedicine in the study by Lea et al, 37 64% received pediatric and/or neurological genetics consultations and the rest received consultations for cancer or reproductive genetics counseling.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in our review related to the use of telegenetics in counseling for hereditary cancer, 26,[28][29][30][31][32][33] prenatal counseling, 34 pediatric services, 35,36 and services for a range of genetic disorders. 24,27,37 Of the 125 patients who were evaluated and/or counseled via telemedicine in the study by Lea et al, 37 64% received pediatric and/or neurological genetics consultations and the rest received consultations for cancer or reproductive genetics counseling.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
“…The patients then returned to the clinic for a face-to-face consultation with the clinical geneticist. Three of the studies explored genetics counseling via teleconference with a genetics counselor only; these comprised one study involving prenatal counseling 34 and two studies involving hereditary cancer counseling. 26,29 Coelho et al, 28 described a study of genetics counseling for cancer via teleconference with a genetics consultant.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
“…[4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care. [9][10][11][12][13][14][15] One study of patient experiences with video visits in rural areas found that they were associated with decreased travel costs and lost time/wages, increased access to social support, and better ability to tailor care delivery to patient and family needs. 16 Because of these benefits, video visits are being adopted in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports suggest that telegenetic care can be useful, patient-friendly, effective and psychologically acceptable for various indications in the light of economic and personnel scarcity on the one hand, and increasing awareness and counselling requests from patients spread over a large geographical area on the other hand. [1][2][3][4][5][6][7] So far, almost all reports of telegenetics programmes described counselling between professionals at a central clinic and patients at regional clinics, with a genetic counsellor present, in regions with large travelling distances. [1][2][3][4][5][6][8][9][10][11] Our pilot project differs from previous reports by (1) counselling sessions taking place in patients' homes, (2) covering patients in a non-remote area and (3) having cardiogenetic as well as previously reported oncogenetic and prenatal counselling.…”
Section: Introductionmentioning
confidence: 99%